the influence of giving katu’s leaf extract fraction toward prolactin level of breastfeeding mice and neuralgia cells of young mice - Kamariyah, Nurul (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2012)
People knew that Sauropus androgynus (L) Merr (katu’s leaf) have good nutrient and can enhance breast milk production. Study about influence of giving katu’s leaf extract fraction toward prolactin level and neuralgia cells in mice is not available recently. The purpose of this study is to find out the influence of giving katu’s leaf extract fraction toward prolactin level and neuralgia cells at mice, and influence prolactin level in breast feeding mouse towards amount of neuralgia cells in mice. Method of this study is laboratories experiment ”the post test-only control group” type experimental animals is mouse (Rattus norvegicus). The samples are 24 breast feeding mice with body weight 150-200 gram and divided into 4 groups, that are control group and treatment group which is given katu’s leaf extract fraction. Treatment group 1 with the dosage 24 mg, treatment group 2 with the dosage 48 mg and treatment group 3 with the dosage 72 mg. Treatment begun at the 3rd day post delivery until the 11th day. The 12th day the mouse is killed, blood from pericardium taken for prolactin test, while the mice is killed and it’s brain made as substance for testing of amount of neuralgia cells. Study result of prolactin with One Way Anova got significant difference (ρ=0,000). Continued with Post Hoc test got significant difference at C–T2, C–T3, T1–T2, T1–T3, and T2–T3. Result of neuralgia cells test at One Way Anova got significant difference (p=0,000).  Continued with Post Hoc test got significant difference at C–T2, C–T3, T1–T2, T1–T3, and T2–T3. Result of linier regression test got ρ (0.940) > α (0,05), means there is no influence prolactin level in breast feeding mouse towards amount of neuralgia cells in mice. The conclusion of the study was prolactin level in breast feeding mouse and amount of neuralgia cells in mice after giving katu’s leaf extract fraction have prolactin level higher and amount of neuralgia cells increase at the dosage 48 and 72 mg. If this study will be applied to human, should be done laboratorial test. More study about containing of breast milk after giving katu’s leaf extract fraction need to be continued.